Effect of Brand Equity on Buying Intention Online Transportation (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of brand equity on the buying intention of online Ojek transportation service customers. Our hypothesis is that the customer prefers to brand equity affects the interest in using online transportation. To answer the problem in this study, researchers used a sample of 100 respondents with data analysis techniques using simple regression analysis. According to research conducted by Brand Image on Purchase Interest is very influential, where according to the above data results have shown that Go-Jek still dominates market share. The percentage of Go-Jek's consumer interest that is greater than that of Grab's consumers. The results of this study are directly proportional to the previous empirical data.